THE EFFECT OF FLEXIBILITY EXERCISE ON FATIGUE SCORE AND BLOOD PRESSURE IN HEMODIALYSIS PATIENTS AT HOSPITAL X, SERANG DISTRICT - Esterlise Nainggolan, Marischa Wanti; Widani, Ni Luh; Supardi, Sudibyo (Universitas Pelita Harapan, 2025)
Chronic kidney failure is becoming increasingly common and rising annually. Patients in stage five require hemodialysis or kidney transplantation due to the risk of blood pressure instability and fatigue. This study aimed to analyze the effect of flexibility exercise on reducing fatigue scores and blood pressure in hemodialysis patients at